SOME COMMENTS ON THE STATEMENT OF PLANNING COSTS. - Wallace, Edward L. (The Accounting Review, 1957)
Abstract When the present Committee On Costs And Standards was formed several years ago in the U.S. it was charged it with the responsibility for developing a statement of cost concepts without specifying either the objectives or content of that statement. For many reasons development of a statement paralleling those issued by the Association on accounting principles underlying corporate financial statements was abandoned in favor of a more general statement relevant to management purposes. This decision reflected an awareness of the growing importance in accounting of the management viewpoint and the lack of any statement of sufficient general validity to perform for management costing the same functions presents statements on accounting principles do for income determination. Rapid developments in recent years in other disciplines have placed a premium upon proper cost constructions. Statistical decision theory, linear programming, mathematical prograimning, waiting line theory, input-out-put analysis, and the like all depend upon accounting for cost data relevant to purposes other than income determination.